Internal knowledge transfers in multinational corporations: a systematic literature review - Castro, Rita Marques (2021)
In the current marketplace, characterised by globalisation, proliferation of technology and hostile competition, the exploitation and management of internal knowledge in companies has become the best vehicle for ensuring a differentiated international positioning, developing organisational knowledge bases, improving performance and growth, as well as to increase market responsiveness. Multinational companies face even more challenges in these processes, since they have to manage multiple knowledge transfers between headquarters and subsidiaries, among subsidiaries, and also within each of these units, in very different cultural, geographic and economic scenarios. Therefore, the aim of this dissertation is to deepen the knowledge about this phenomenon and to uncover the main influencing factors on internal knowledge transfers in multinational companies. Apart from including intra-unit knowledge transfers, this dissertation also analyses transfers between units, namely conventional, horizontal and reverse knowledge transfers. For this purpose, a systematic review of the literature was conducted to synthesise the content of 72 articles. Conclusions were drawn regarding the most recurrent publication years and sources, theoretical foundations, research methods, countries and industries in the literature. Moreover, this dissertation allowed to summarise the results for each type of knowledge transfer, identifying eight thematic categories and 97 topics covered in the literature, thus creating a complete framework of this phenomenon. Some gaps in the literature and contributions to theory, research and management are also highlighted, which will help to advance knowledge in these fields.